2022
DOI: 10.3390/vaccines10040577
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Recommended HPV Vaccine Dosing Schedule among Adolescents Aged 13 to 17 Years: Findings from the National Immunization Survey-Teen, 2019–2020

Abstract: The 9-valent human papillomavirus (9-vHPV) vaccine uptake rate among adolescents has improved over the years; however, little is known about the adherence to the recommended dosing schedule. This study examines the prevalence and factors associated with adherence to the recommended 9vHPV vaccination dosing schedule among adolescents aged 13 to 17 years. The cross-sectional study was conducted using the 2019–2020 National Immunization Survey-Teen. The parents of 34,619 adolescents were included in our analyses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…37 Also, studies have shown that patients from low-income families are more likely to initiate and complete the HPV vaccines. 9 , 36 More so, our data show that HCPs in FQHCs see more patients than those in teaching hospitals and that seeing a high number of patients positively correlates with HPV vaccination status assessments and recommendations. Overall, our study highlights important opportunities for HCPs to be adequately prepared and equipped with tools to address patient concerns and counsel, promote, and recommend HPV vaccination at every visit.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…37 Also, studies have shown that patients from low-income families are more likely to initiate and complete the HPV vaccines. 9 , 36 More so, our data show that HCPs in FQHCs see more patients than those in teaching hospitals and that seeing a high number of patients positively correlates with HPV vaccination status assessments and recommendations. Overall, our study highlights important opportunities for HCPs to be adequately prepared and equipped with tools to address patient concerns and counsel, promote, and recommend HPV vaccination at every visit.…”
Section: Discussionmentioning
confidence: 67%
“… 35 Nationally, it has also been noted that Hispanic adolescents are more likely to receive HPV vaccines. 9 , 36 Consequently, Hispanic HCPs who are more likely to see Hispanic patients/parents may often assess HPV vaccination status and recommend vaccination based on their Hispanic patients’ general willingness to receive the vaccine. 9 , 35 , 36 Also, we found that nurses and physician assistants were less likely than physicians to assess vaccination status and recommend the HPV vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adherence to the recommended dosing schedule for HPV vaccine is also important for adequate immune response and expected protection from HPV-associated diseases. 43 Since younger adolescents have a better immunologic response to the HPV vaccine, this may translate into improved effectiveness. 44 Emphasizing routine administration of the HPV vaccination at age 11–12 has shown to increase parents’ preference for on-time vaccination and improves adherence to the dose scheduling.…”
Section: Discussionmentioning
confidence: 99%
“…44 Emphasizing routine administration of the HPV vaccination at age 11–12 has shown to increase parents’ preference for on-time vaccination and improves adherence to the dose scheduling. 43 , 45 Previous research has shown that framing recommendations involving fewer doses before age 15 may discourage on-time HPV vaccination and suggest to parents that routine HPV vaccine administration extends to this age. 45 …”
Section: Discussionmentioning
confidence: 99%